Letter from Carl D. Duncan to Patricia Whiting, January 22, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan compliments Whiting on her beauty and expresses concern that she may not always be safe. Duncan also mentions Whiting's family.